Features of foreign experience of micro-insurance for insurance market in Ukraine - Arych, Mykhailo (My University, 2017)
The paper investigates the advanced foreign experience of micro-insurance organization. The possibility and advantages of using the experience of micro-insurance in the countries of Europe, Central and South America, Asia for the insurance market of Ukraine are analyzed. The conducted research showed that the current state of micro-insurance development in highly developed countries of the world has many advantages over the development of micro-insurance in Ukraine. Therefore, we consider it necessary to build a Ukrainian model of micro-insurance taking into account the best foreign experience, using highly effective methods of its application and implementation in practice.
Keywords: micro-insurance; insurance market; insurance premium; competitiveness; мікрострахування; страховий ринок; страхова премія; конкурентоспроможність; кафедра фінансів